Corporate Social Responsiveness: Studi Naratif Success Story Transisi Pengalihan Kepemilikan Perusahaan dari Devon Energy Companies in Ind - Thalib, Suganda; Thoyib, Armanu; Surachman (Jurnal Aplikasi Manajemen, 2014)
The purposes of research are to: (1) identify role from three regulators namely; CSR Driver, CSR Internal Tools and CSR Enabler in influencing critical incident to the company; (2) identify initiative strategy CSR or CSR outcomes in handling the critical incident; and (3) proposed a Model for regulating the critical incidents. This research conduct in depth analysis and examine over one case of success story in handling the critical incident that occurred during transition of stockholder changeover from Devon Energy Companies in Indonesia (DECI) to PetroChina International Companies in Indonesia (PCI). This Research uses the multiple data that are Combining Historical Research and Narrative Inquiry to understand the phenomenon of success story. In this research; key-informans are interviewed to obtain their narratives; and document correspondent and media released are used as sources for constructing the chronicles. Data is analyzed by using Domain, Taxonomic and Componential Analysis. The result of this research indicates: (1) Factors that considered as CSR regulators is; 1a.Transformer, formed factors that lead to improve emphasis to the employee's demand about compensation payment to the company transfer from DECI to PCI; 1b. Rectifier, formed factors that have a role to support, measure and help in handling the employee's demand about compensation payment to the company transfer from DECI to PCI; and 1c.Capacitor/Smoothing, formed factors that have a role to give references/standard in handling the employee's demand about compensation payment to the company transfer from DECI to PCI. (2) DECI's CSR Management could not handle the employee's demand, so that they utilized external parties and involved stakeholder to broke the law and regulation impasse about labour and existing working-agreement betweenemployee and company (3) Proposed a Model about arrangement mechanism on critical incident by CSR Regulator, which is refer to this model by using response strategy of CSR Surgery, time required to handle the employee's demand about compensation payment to the company transfer from DECI to PCI d is not longer than one month from April 16 thru May 17, 2002.